Creating Community: Industrial Paternalism and Town Planning in Corner Brook, Newfoundland, 1923–1955 - White, Neil (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2004)
In the early twentieth century numerous primary extractive industries constructed company towns on the resource frontiers of North America. Company directors hoped that massive capital infusion in remote areas in the form of planned towns would secure a much-needed skilled workforce and generally increase returns. The pulp and paper town of Corner Brook in western Newfoundland is a significant, but largely neglected case in point. This paper details the paternalist and utilitarian motivations of companies for single-industry community construction at this time. More importantly, however, it offers a new and critical approach to the issue of single-industry community development. Early multinational companies sought to secure a place "on the ground" through comprehensive planning and community administration. At the same time, residents of Corner Brook, though constrained by dependence on the sole industry, negotiated their own physically and socially distinct community in a variety of ways. The global-local nexus of company planning, resident response, and change introduces a complexity into the study of company towns that are generally portrayed in terms of rigid top-down company exploitation of a "captive" workforce.